Sharko and Hippo - Kalan, Elliott, 1981- (Balzer + Bray, an imprint of HarperCollinsPublishers, 2020)
"When Sharko calls for a boat, Hippo pulls out a goat. He wants a pole, but Hippo gives him a pail. And instead of bait, a beet and a boot! Hippo's coat pockets seem to have everything except what Sharko asks for!"--Jacket flap.